2015
DOI: 10.1126/scisignal.aab0990
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathway models as biomarkers: Patient-specific simulations of JNK activity predict the survival of neuroblastoma patients

Abstract: Signaling pathways control cell-fate decisions that ultimately determine the behavior of cancer cells.Therefore, the dynamics of pathway activity may contain prognostically relevant information different from that contained in the static nature of other types of biomarkers. To investigate this hypothesis, we characterized the network that regulated stress signaling by the Jun N-terminal kinase (JNK) pathway in neuroblastoma cells. We generated an experimentally calibrated and validated computational model of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(204 citation statements)
references
References 74 publications
5
191
0
1
Order By: Relevance
“…The advantage of using such personalised dynamic models over static biomarkers, has already been demonstrated in several case studies (Fey et al, 2015;Flanagan et al, 2015;Murphy et al, 2013;Lindner et al, 2013). In contrast to previous approaches, the here proposed methodology is not restricted to models in which the total protein concentrations are time-invariant parameters.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The advantage of using such personalised dynamic models over static biomarkers, has already been demonstrated in several case studies (Fey et al, 2015;Flanagan et al, 2015;Murphy et al, 2013;Lindner et al, 2013). In contrast to previous approaches, the here proposed methodology is not restricted to models in which the total protein concentrations are time-invariant parameters.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, multiple studies have shown that patient-specific differences in the dynamic behaviour of these signalling networks underlie individual pathogenetic changes and disease manifestation (Fey et al, 2015;Flanagan et al, 2015;Lindner et al, 2013;Murphy et al, 2013). For example, a dynamic model of the JNK pathway could predict the survival probabilities of cancer patients in neuroblastoma, a common childhood cancer (Fey et al, 2015). These predictions were based on personalised simulations for over 700 patients, and revealed that a high amplitude, switchlike JNK activation was associated with neuroblastoma cell death, and better patient survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, exome transcriptome sequencing data of cancer cell lines have been used to set cell line-specific translation rates [64,65]. In a similar study, the mRNA expression was used to predict the survival of individual neuroblastoma patients [66]. While both approaches were successful in the respective applications, transcription rates and mRNA levels can change in response to treatment.…”
Section: Personalization Of Models Using Datamentioning
confidence: 99%
“…The development of multivariate biomarkers for diagnostic assays could allow more patients to benefit from improved drug regimens. Ultimately, such multivariate markers could be implemented in a dynamic manner, if for example integrated with circulating tumor cell (CTC) techniques so as to monitor patient response and tumor dynamics on treatment [38,39] . Our work described here provides a case study of integrating experimental data generated using multivariate profiling technologies with a variety of computational modeling and simulation methods to interpret such measurements and make clinical predictions on their therapeutic utility.…”
Section: The Future Of Biomarker Identificationmentioning
confidence: 99%